2013
DOI: 10.1002/jcla.21638
|View full text |Cite
|
Sign up to set email alerts
|

Anticyclic Citrullinated Peptide Antibody and Rheumatoid Factor in South Tunisian Patients With Rheumatoid Arthritis: Association With Disease Activity and Severity

Abstract: These findings suggest that anti-CCP antibodies are associated with RF and more severe joint damage. Moreover, disease activity is associated with functional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Likewise among the clinical laboratory findings, both the presence of RF and erosions were found to be associated with RA. Similar findings have been cited in the literature that higher ACCP levels are associated with progressive and erosive joint damage [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 89%
“…Likewise among the clinical laboratory findings, both the presence of RF and erosions were found to be associated with RA. Similar findings have been cited in the literature that higher ACCP levels are associated with progressive and erosive joint damage [11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 89%
“…However, joint pain is often present before the onset of joint inflammation, a time when autoantibodies are also detected [20], suggesting a possible link between the two, irrespective of clinical inflammation. In agreement with a role in joint pain, one study showed that the presence of ACPAs positively correlated with pain scores [21].…”
Section: Key Pointsmentioning
confidence: 89%
“…Abnormal levels of RF and anti-CCP antibodies indicate that the patient has a severe condition with a rapid progression, as well as severe bone destruction. 16 This indicates that IL-37 levels have a distinct correlation with the severity of RA.…”
Section: Discussionmentioning
confidence: 97%